2018
DOI: 10.1101/419986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who gets lost and why: A representative cross-sectional survey on sociodemographic and vestibular determinants of wayfinding strategies

Abstract: 2 When we think of our family and friends, we probably know someone who is good at finding 3 their way and someone else that easily get lost. We still know little about the biological and 4 environmental factors that influence our navigational ability. Here, we investigated the 5 frequency and sociodemographic determinants of wayfinding and their association with 6 vestibular function in a representative cross-sectional sample (N = 783) of the adult German-7 speaking population. Wayfinding was assessed using t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Figures 1g-h represent the effect of the environment on W F stratified by age, gender, and education. We replicate previous studies showing that wayfinding performance decreases with age [27,28], males perform better than females [29], and performance increases with the level of education [30,31]. Here we now report that participants raised outside cities are more accurate navigators than city-dwellers.…”
Section: Resultssupporting
confidence: 90%
“…Figures 1g-h represent the effect of the environment on W F stratified by age, gender, and education. We replicate previous studies showing that wayfinding performance decreases with age [27,28], males perform better than females [29], and performance increases with the level of education [30,31]. Here we now report that participants raised outside cities are more accurate navigators than city-dwellers.…”
Section: Resultssupporting
confidence: 90%
“…In accordance with the hypothesis and previous literature, gender bias on the SBSODS was also identified. Males appraised their SOD (on average) significantly higher than their female counterparts (Castelli et al, 2008), despite non‐significant navigation task performance differences across genders (Coluccia & Louse, 2004; Nori & Piccardi, 2015; Picucci et al, 2011; Torres‐Guijarro & Bengoechea, 2016; Ulrich et al, 2019). Nori and Piccardi (2015) speculated that the underestimation of spatial abilities in females might stem from the fact that they typically require a longer learning time than males (Nori et al, 2018; Piccardi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While clinical assessment of everyday navigation abilities relies predominantly on self‐reports, evidence continues to question their validity and reliability (Meade et al, 2019; Munion et al, 2019; Ventura et al, 2013). For instance, it has been found that males consistently overestimate their navigation ability despite performing similarly to females on many objective route‐tracking tasks (Castelli et al, 2008; Coluccia & Louse, 2004; Torres‐Guijarro & Bengoechea, 2016; Ulrich et al, 2019). Furthermore, van der Ham et al's (2021) comparison of self‐reported versus objective navigation abilities revealed systemic gender and age biases—with increasing ability overestimation as a function of age.…”
Section: Introductionmentioning
confidence: 99%